Preserving Isnad in the Algorithmic Era: A Mosque-Based Hybrid Educational Communication Model - Samsuriyanto Samsuriyanto (CV. Kayaswara, 2026)
Background: Technological disruption in the digital era drives mosque institutions to adopt Artificial Intelligence (AI) to speed up information dissemination and educational communication. However, uncontrolled AI integration triggers an isnad crisis and a loss of spiritual essence due to the algorithm’s inability to validate the intellectual lineage of teachers. Research Objective: This study aims to formulate an effective, theologically sound, and adaptive hybrid educational communication model to preserve the authenticity of knowledge in mosques during this algorithmic era. Methods: This study utilizes a qualitative approach with a library research design, gathering reputable literature (2016-2026), and analyzing data using the Interactive Model of Miles, Huberman, and Saldaña. Results: This study formulates the Mosque-Based Hybrid Educational Communication Model based on the human-in-the-loop principle. This model establishes a strict demarcation line: AI is positioned downstream merely as a technical acceleration assistant (design, scheduling, distribution), while the upstream domain (defining legal substance, interpreting texts, final validation) remains absolutely controlled by an expert council or scholars possessing a clear isnad through integrated pre-production, production, and post-production mechanisms. Conclusion: This micro-operational hybrid framework proves that technological modernity and intellectual orthodoxy can be harmoniously integrated for the community’s benefit, serving as a tactical guide for mosque managements to safely expand da’wah reach without compromising the purity and authenticity of Islamic teachings.